CAUSES OF ACNE IN ADOLESCENTS WITH DIABETES MELLITUS - Mirabbos Rustamov (Web of Journals Publishing, 2025)
Objective: To study the relationship between diabetes mellitus and the development of acne in adolescents, as well as to identify the specific pathophysiological mechanisms underlying these processes. Methods: A review of current research on dermatological manifestations in adolescents with diabetes mellitus, with an emphasis on acne, has been conducted. The analysis included articles from the databases PubMed, Scopus and eLibrary for 2019-2024. Results: A close relationship has been established between insulin resistance, hyperglycemia, and sebaceous gland activation. The role of hormonal and immune disorders in diabetes in the pathogenesis of acne has also been revealed. Conclusions: Adolescents with diabetes are at higher risk of developing acne than their healthy peers. An individual approach to acne treatment is needed in this group of patients.
Keywords: acne, adolescents, diabetes mellitus, insulin resistance, sebaceous glands, inflammation, hyperglycemia.